2013
DOI: 10.1016/j.cognition.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Rational snacking: Young children’s decision-making on the marshmallow task is moderated by beliefs about environmental reliability

Abstract: Children are notoriously bad at delaying gratification to achieve later, greater rewards (e.g.,Piaget, 1970)—and some are worse at waiting than others. Individual differences in the ability-to-wait have been attributed to self-control, in part because of evidence that long-delayers are more successful in later life (e.g., Shoda, Mischel, & Peake, 1990). Here we provide evidence that, in addition to self-control, children’s wait-times are modulated by an implicit, rational decision-making process that considers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
295
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 346 publications
(332 citation statements)
references
References 29 publications
13
295
0
12
Order By: Relevance
“…Greed may thus to ensure future resource access and eliminate uncertainty. In support, a recent study indicates that, when children are unsure about future access to resources, they tend to opt for instant gratification (Kidd, Palmeri, & Aslin, 2013). If greed serves this purpose, why do people differ in how greedy they are?…”
Section: Discussionmentioning
confidence: 80%
“…Greed may thus to ensure future resource access and eliminate uncertainty. In support, a recent study indicates that, when children are unsure about future access to resources, they tend to opt for instant gratification (Kidd, Palmeri, & Aslin, 2013). If greed serves this purpose, why do people differ in how greedy they are?…”
Section: Discussionmentioning
confidence: 80%
“…low selfcontrol) prevents more overall burden of disease than targeting only individual people at high risk [40]. However, preterm children may not only have lower inhibitory control abilities than full term children but may also be more vulnerable to environmental influences further decreasing their abilities to inhibit undesirable responses [41,42]. As our findings apply to the whole GA spectrum of preterm and full term children, it may thus be recommended to adopt a combination of both population and targeted approaches to interventions in order to achieve the highest benefits [43].…”
Section: Discussionmentioning
confidence: 99%
“…Kidd, Palmeri, and Aslin (2013), found that children's ability to delay gratification to receive greater awards was affected by the reliability of the experimenter and perhaps of the testing situation. Children were originally told that they could play with some old, used materials or wait until the researcher brought to the room more exciting, brand-new materials.…”
Section: When Children Encounter Message Conflicts: Other Observationsmentioning
confidence: 97%